Origami in the 3D space

Geometry Level 3

Above is the rectangle A B C D ABCD , where A D = 4 , A B = 2 2 AD=4, AB=2\sqrt{2} , and F , E F,E are the midpoints of B C , C D BC, CD respectively.

If we fold A E D \triangle AED along A E AE in the 3D space to A E M \triangle AEM so that M E M F ME \perp MF , as shown above, then find the dihedral angle M A E F M-AE-F . Submit the angle in degrees and round to the hundredth.


The answer is 60.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

David Vreken
Jun 1, 2020

Let the coordinates of M M be ( x , y , z ) (x, y, z) . Then by the distance formula, M E = 2 = ( x 4 ) 2 + ( y 2 ) 2 + z 2 ME = \sqrt{2} = \sqrt{(x - 4)^2 + (y - \sqrt{2})^2 + z^2} , M F = 2 = ( x 2 ) 2 + y 2 + z 2 MF = 2 = \sqrt{(x - 2)^2 + y^2 + z^2} , and M A = 4 = x 2 + ( y 2 2 ) 2 + z 2 MA = 4 = \sqrt{x^2 + (y - 2\sqrt{2})^2 + z^2} , which solves to M ( x , y , z ) = M ( 10 3 , 2 2 3 , 2 3 3 ) M(x, y, z) = M(\frac{10}{3}, \frac{2\sqrt{2}}{3}, \frac{2\sqrt{3}}{3}) for z > 0 z > 0 .

The equation of the plane with A A , E E , and M M can be expressed generally as x + b y + c z = d x + by + cz = d . A ( 0 , 2 2 , 0 ) A(0, 2\sqrt{2}, 0) gives 2 2 b = d 2\sqrt{2}b = d , E ( 4 , 2 , 0 ) E(4, \sqrt{2}, 0) gives 4 + 2 b = d 4 + \sqrt{2}b = d and M ( 10 3 , 2 2 3 , 2 3 3 ) M(\frac{10}{3}, \frac{2\sqrt{2}}{3}, \frac{2\sqrt{3}}{3}) gives 10 3 + 2 2 3 b + 2 3 3 c = d \frac{10}{3} + \frac{2\sqrt{2}}{3}b + \frac{2\sqrt{3}}{3}c = d , which solves to x + 2 2 y + 3 z = 8 x + 2\sqrt{2}y + \sqrt{3}z = 8 .

The equation of the plane with A A , E E , and F F is z = 0 z = 0 .

The normal to x + 2 2 y + 3 z = 8 x + 2\sqrt{2}y + \sqrt{3}z = 8 is ( 1 , 2 2 , 3 ) (1, 2\sqrt{2}, \sqrt{3}) and the normal to z = 0 z = 0 is ( 0 , 0 , 1 ) (0, 0, 1) . The angle θ \theta between these normals (and also the dihedral angle between the two planes) is θ = cos 1 ( ( 1 , 2 2 , 3 ) ( 0 , 0 , 1 ) 1 2 + ( 2 2 ) 2 + ( 3 ) 2 0 2 + 0 2 + 1 2 ) = cos 1 ( 1 2 ) = 60 ° \theta = \cos^{-1} ( \frac{(1, 2\sqrt{2}, \sqrt{3}) \cdot (0, 0, 1)}{\sqrt{1^2 + (2\sqrt{2})^2 + (\sqrt{3})^2} \cdot \sqrt{0^2 + 0^2 + 1^2}}) = \cos^{-1} (\frac{1}{2}) = \boxed{60°} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...